2015
DOI: 10.11002/kjfp.2015.22.6.831
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of edible cricket (Gryllus bimaculatus) in different districts

Abstract: Insects have gained increasing attention as an alternative protein and nutrient rich food source for humans. This study was conducted to investigate the physicochemical characteristics and harmful components of edible crickets (Gryllus bimaculatus) in the 6 districts of Yeonggwang (YG), Jeongseon (JS), Wonju (WJ), Hwaseong (HS), Geochang (GC), and Chungju (CJ). The average crude protein and crude lipid contents on a dry basis were 64.34% and 16.60%, respectively. The crude protein content of CJ was the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…The results also showed that the proportion of UFAs was 65.79%, mainly consisting of oleic acid (22.75%) and linoleic acid (41.75%), the proportion of saturated fatty acids (SFAs) was 34.21%. Compared with the previously reported results on the analysis of fatty acids in Gryllus bimaculatus [26,27], the composition and content of main fatty acids were consistent, except for a trace of arachidic acid (C20:0) and arachidonic acid (C20:1), which were not detected in the present study.…”
Section: Fatty Acid Compositions Of Raw Gryllus Bimaculatus and Palm Oilsupporting
confidence: 71%
“…The results also showed that the proportion of UFAs was 65.79%, mainly consisting of oleic acid (22.75%) and linoleic acid (41.75%), the proportion of saturated fatty acids (SFAs) was 34.21%. Compared with the previously reported results on the analysis of fatty acids in Gryllus bimaculatus [26,27], the composition and content of main fatty acids were consistent, except for a trace of arachidic acid (C20:0) and arachidonic acid (C20:1), which were not detected in the present study.…”
Section: Fatty Acid Compositions Of Raw Gryllus Bimaculatus and Palm Oilsupporting
confidence: 71%